KOMPETENSI PROFESIONAL GURU GEOGRAFI SEKOLAH MENENGAH ATAS DI KOTA LHOKSEUMAWE - Tarakavita, Cut Dian (2014)
Teacher professional competency is the ability of mastery learning material is wide and deep, which allows the guiding of students meet the standard of competence specified in the national standards of education. Professional competence is essential in order to realize the role of geography as a subject that has the role of the realization of the goals of national education. Teachers who teach at each school certainly has different professional competence. For that this research was conducted to find out the professionalism of teachers, especially in terms of; (1) control of the materials, structure, concepts and scientific mindset (2) Standards of competence and mastery of Basic competencies, (3) Developing Creative Material (4) self development in a professional manner (5) utilization of, information and Communication Technology in learning. The method used is descriptive method. The population is all of high school geography teacher Lhokseumawe and the sample amounted to 16 people. Variable teacher professional competency is research, mastery of the material, the mastery of Standard of Competency and Basic Competency, developing the material creatively, Professionality development and utilization of information and communication technology. Instruments using instrument test and questionnaire. Based on the results of the research note that mastery of the material, structure and scientific concepts, belongs to the category simply mastering, mastering the Basic Competencies and Competency Standards are included in the category simply overwhelms, developing creative materials are included in the category quite developed; development of professionalism included in the category quite a developed professionalism and utilization of ICT is included in the category quite harness. The shortage that prominently is mastery of the material, structure and scientific concepts , implementation of the Class Action Research and the unoptimal utilization of ICT so that on this very aspect needs to be improved. Keyword: Competence, Teacher Professional, Geography